Exploring the Knowledge and Practice of Water Conservation Measures: A Case of Low-Cost Housing Setting in South Africa - Thakur, Rookmoney; Onwubu, Stanley; Harris, Geoffrey (African Journal of Inter/Multidisciplinary Studies, 2021)
The water crisis has reached a fever pitch in South Africa, with threats of ground zero and disruption of water supplies. The paper focuses on household knowledge and awareness of the water crisis and conservation efforts to reduce water consumption in a low-cost housing setting within the eThekwini municipality, KwaZulu-Natal, South Africa. A mixed method that consists of qualitative and quantitative phases was adopted to explore water practices. Focus group discussions were conducted with a representative sample of 22 people residing in the Waterloo area, situated north of Durban. Subsequently, the results from the discussions were used to design a questionnaire which was administered to 304 residents in the same location. Data was collected through an anonymised research questionnaire. The qualitative data was analysed using content analysis by generating codes to theme the data while descriptive analysis was performed on the quantitative data. In synthesising the results, three recurring key issues are identified, namely (1) access to knowledge; (2) community engagement as part of the solution; and (3) allocation of incentives. While participants had knowledge of water conservation practices, there was, however, a high amount of water consumption and high unaccounted water losses in the area. Although some of the participants held the view that providing incentives like free airtime and electricity could help influence water conservation, many were, however, in favour of installing water-harvesting facilities such as JoJo tanks. The study conclusively proposes economic nudging in the LCH areas as a cost-effective measure towards water conservation.